Organizational learning and post-crisis management at Tesla Inc in facing crisis communications - Renadia, Shavira Hanza (International Journal of Communication and Society, 2022)
This article aims to discuss organizational learning and crisis management at Tesla Inc. Digital disruption has made corporate communication required to use agile strategies in dealing with dynamic communication crises. Tesla's communications crisis started with 11 accidents in 2018, and Tesla removed the communications department amid the crisis. The lack of relationship between the media and the company can cause a potential crisis to occur. The disappearance of the communications department has made it difficult for journalists to obtain press releases and made it easier for issues to be uncontrolled. This transformation is a form of organizational learning in facing a crisis and aims to make communication centralized and transparent. Tesla's external communications now use its CEO's Twitter @EllonMusk to communicate with external stakeholders. Tesla's open and innovative corporate culture can influence the company's decisions in dealing with a crisis. This article is analyzed using qualitative methods with a case analysis approach to find solutions to overcome the communication crisis that occurred.